WIZERUNEK PREZYDENTA WŁADIMIRA PUTINA NA PORTALACH SPOŁECZNOŚCIOWYCH (NA PRZYKŁADZIE FACEBOOKA) - Patocka-Sigłowy, Urszuka (Przegląd Rusycystyczny, 2017)
The President Vladimir Putin has been the leader of Russian popularity rankings for years. His strong position in the international arena is emphasised by a number of awards granted by foreign magazines. The number of Facebook pages devoted to that famous politician confirms his phenomenal position in social media. This article focuses on the analysis of the Facebook image of Vladimir Putin.